(untitled) (American Journal of Islam and Society, 2012)
Are dietary religious laws an obstacle to community relations between members of the Abrahamic faiths? The new edition of Pierre Birnbaum’s Le Peuple et Les Gros, under the title Genèse du Populisme (Hachette Pluriel: 2012) explores how eating pork in Paris and other cities can be read as a sign of identity crisis in French society, as a way of excluding from the public space those who are different, in this case Jews and/or Muslims who follow dietary laws forbidding its consumption. Similarly, in Foreigners and Their Food: Constructing Otherness in Jewish, Christian, and Islamic Law, the question of community, religious laws about food, and a thorough analysis of the relevant sacred texts is revealing. This book explores how the Abrahamic faiths conceptualize “us” and “them” through the rules related to food preparation by those who are not “us” and the precise act of eating with “them.” Moreover, it echoes an important marker of how communities remain segregated at meal time even though sharing food is seen as a familial, communal, and, most importantly, a sacred act. Foreigners and Their Food opens with Freidenreich’s personal struggle with food and its significance in deconstructing boundaries between different traditions. The author, an ordained rabbi, readily admits to a bias of comparative analysis when interpreting the texts and laws; however, this admission accentuates and delineates a thorough analysis and rich interpretation that the study of religion is yearning for in intertexual analysis. The book begins with a discussion of “imagining otherness,” one that alerts readers to the significance of food, its symbolic nature of inclusion/ exclusion, and the absence of any analysis as to how it impacts so many religious adherents who rely upon these laws but cannot critically reflect upon them as markers of “us” and “them.” Freidenreich looks at what Leviticus, Deuteronomy, and similar traditional texts state, but he is clearly reaching for meanings that lie beyond the text. He points out as a general theme that “Absent from Biblical passages regarding these dietary laws, however, is any suggestion that the norms enjoined upon Israelites stand in opposition to non-Israelite practices” (p. 21) ...